Otimização de recebimento e distribuição em unidades armazenadoras de soja - Oliveira, Adalberto Luís Rodrigues de (2005)
The following study whose objective is to elaborate a mathematics model to the maximization of the budget coming from the logistics, strategies of acquiring, receiving, storage and distribution process aiming the sale or exportation in order to get a higher price according to the season and presents a computational program. Thus, it was mentioned theoretical features of methods for solving the Localization and outing Problems. Besides that, it was accomplished a more applied detailing of the Routing Method as well as the description of the used form of distribution of soybean by Campagro company. The computational program and its evaluation proposal were applied to a set of data including 494 farmers of Campo Mourão and its region and 7 grains stores. The accomplished model, which considered mainly the clusterization, has shown that the use of such method provides time saving and it considers the smallest distance between the grains stores and the producers.